KELEKATAN ANAK TERHADAP ORANG TUA DALAM PEMBENTUKAN KEMANDIRIAN DI TAMAN KANAK-KANAK AS-SALAM KOTA JAMBI - Zawaqi Afdal Jamil; Miari Edlin Kuswardani (Generasi Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2020)
This research was conducted based on the findings of children's behavior tendencies less independent. The research objectives were to determine the understanding of parents towards attachment and urgency, the duration of time with parents and children, and optimal coordination between parents and teachers in shaping children's independence in As-Salam Kindergarten, Jambi City. This research used a qualitative descriptive method which was conducted in As-Salam Kindergarten, Jambi City. The research subjects were parents (mothers) of As-salam Kindergarten children, Jambi City. Methods of data collection are carried out by observation, interviews, and documentation. The research instrument is the researcher as a key instrument. The data collected were analyzed using a flow data analysis model, namely data reduction, presentation, and conclusion. The results of the study revealed that the lack of parental understanding of attachment and urgency, the lack of time between children and mothers to make children, and less optimal coordination between teachers and parents. Analysis of these findings shows that children are less independent.